Infrared thermography as a tool for measuring water stress index in avocado cultivars (Persea americana M.) - Ramos-Fernández, Lia (2024)
Introduction. Avocado cultivation is susceptible to water stress during the flowering stage and initial fruit growth. This stress can cause premature fruit drop and accentuate the alternation in production. Objective. To determine the crop water stress index (CWSI) in three avocado cultivars (Hass, Fuerte, and Zutano) under different irrigation conditions using infrared thermography. Materials and methods. The study was conducted in the autumn of 2023, at the Estación Experimental Agraria Canaán, Ayacucho, Peru. A total of 170 four-year-old avocado trees in the reproductive phase were selected. Five evaluations were carried out under different irrigation conditions, where data was collected after 14 and 7 days without irrigation (WI-14d and WI-7d) and at 12, 2, and 1 hour post-irrigation (AI-12h, AI-2h, and AI-1h, respectively). Leaf temperature (Th), stomatal conductance (gs), soil moisture (θ), and CWSI were recorded. Results. The three evaluated cultivars showed significant differences in Th depending on the irrigation management. These variations, influenced by ambient temperature and humidity, established stress thresholds that defined the CWSI within a range of 0.34 to 0.96. By correlating the CWSI with gs and θ, values of R2 = 0,51 y R2 = 0,61 were obtained, respectively. The Zutano cultivar exhibited the highest CWSI values during prolonged water restriction periods and showed a limited ability to reduce these values after rehydration, differing from the other cultivars. Conclusions. Infrared thermography proved to be an effective too for measuring the CWSI in avocado cultivars, reveling significant variations in Th based on irrigation conditions. Adicionally, the Zutano cultivar was the lest resilient to water stress.